Joe's Showboat - Yates, Irene (Ladybird Books Ltd, 2000)
A story which is designed to help beginner readers grasp the important link between sounds and the letters that represent them. Joe's Showboat features a boat, a goat, a show and a lot of snow.
Keywords: Action & Adventure; General; Juvenile Fiction